2020
DOI: 10.1590/s1678-9946202062008
|View full text |Cite
|
Sign up to set email alerts
|

Access and adherence to isoniazid preventive therapy and occurrence of active TB in a cohort of people living with HIV: a retrospective cohort study in Sao Paulo, Brazil

Abstract: Tuberculosis (TB) is still a leading cause of morbidity and mortality among people living with HIV (PLHIV). The diagnosis of latent TB is required for the implementation of prophylactic therapy with isoniazid (PTI). However, low access to diagnosis of latent TB and non-adherence to PTI may hinder potential benefits of this essential intervention. In this study, we addressed the access and adherence to PTI in a cohort of PLHIV with positive tuberculin skin test (TST) in a reference HIV clinic in Sao Paulo, Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Primary outcomes Isoniazid vs. placebo or non-treatment Two NRSs compared the e cacy between isoniazid and non-treatment in 470 participants. The e cacy was similar in the two groups (OR: 0.62; 95%CI 0.17-2.26) (19,20). However, most active TB patients in isoniazid group in Picone et al's study were non-adherent to therapy (6 of the 14 non-adherent patients suffered active tuberculosis).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 83%
See 1 more Smart Citation
“…Primary outcomes Isoniazid vs. placebo or non-treatment Two NRSs compared the e cacy between isoniazid and non-treatment in 470 participants. The e cacy was similar in the two groups (OR: 0.62; 95%CI 0.17-2.26) (19,20). However, most active TB patients in isoniazid group in Picone et al's study were non-adherent to therapy (6 of the 14 non-adherent patients suffered active tuberculosis).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 83%
“…In one trial, the non-treatment group being compared with the isoniazid group had variable "literacy" and "illicit drug use", and the adherence to isoniazid was self-reported (19). The reason why patients didn't receive prophylactic therapy in the other studies is not clear, however some patients with liver disease have concerns regarding the safety of isoniazid (20).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Three of the included studies did not report where they were conducted 54 , 62 , 88 . The most frequent settings were: outpatient clinics and clinics (n = 41) 24 - 26 , 30 , 35 - 38 , 40 - 43 , 46 - 52 , 56 - 58 , 61 , 67 , 68 , 71 - 73 , 75 , 81 , 82 , 84 , 85 , 87 , 89 - 95 ; hospitals (n =19) 24 , 28 , 39 , 40 , 45 , 53 , 55 , 59 , 60 , 64 , 66 , 70 , 74 , 76 , 77 , 80 , 78 , 79 , 83 ; and penitentiaries (n = 4) 29 , 31 , 33 , 63 .…”
Section: Resultsmentioning
confidence: 99%
“…Most of the included studies (n = 49) did not specify patient profiles 24 - 33 , 35 - 37 , 40 - 44 , 47 , 49 , 51 , 52 , 54 , 55 , 57 - 59 , 60 , 63 - 65 , 67 , 68 , 70 , 71 , 77 , 79 , 81 - 87 , 89 , 90 , 93 , 94 , four studies involved patients with inflammatory bowel disease or immune-mediated inflammatory diseases 72 , 73 , 76 , 80 , four involved human immunodeficiency virus (HIV)-positive adults 56 , 61 , 74 , 91 , four involved patients who transplanted or had transplants 34 , 50 , 62 , 66 , and six involved health professionals 38 , 39 , 45 , 48 , 78 , 88 .…”
Section: Resultsmentioning
confidence: 99%
“…In TB cases caused by M. tuberclosis mycrobacteria in the past, with the development and use of antimicrobials, mortality rates decreased significantly and TB ceased to be an important public health. However, as a result of the development of multi drug resistant TB and extensive drug resistant TB and the increase of immune system disrupting diseases such as HIV, TB has become one of the most important global health problems and deaths caused by infections [17][18][19][20] . In our study, according to WHO ICD-10 data, it was observed that tuberculosis-related deaths were reported in 14 countries in the world, of which 12 countries had tuberculosis-related deaths over a year.…”
Section: Discussionmentioning
confidence: 99%